Effects of Stem Design on the Mechanical Behavior of Femur with Total Hip Arthroplasty - Wu, Shun; Todo, Mitsugu (International Journal of Orthopedics and Rehabilitation, 2021)
Total hip arthroplasty (THA) is a common orthopedic surgery, and almost only choice for those patients who suffer severe osteoarthritis. Zweymüller stem, one of the most reliable stems, is considered to be appropriate for elderly patients. However, the structural effectiveness of trochanteric shoulder for primary stability has not been clear yet. This research intended to perform a finite element analysis to explore the necessity of trochanteric shoulder for the primary stability. Realistic simulation models with a femoral bone model and three stem designs were carefully constructed. Analysis of relative sliding micromotion between bone and stem revealed that the shoulderless design has an acceptable primary stability. It was also suggested that the proximal broad design could be unnecessary for rectangular diaphyseal-fixation stems. This kind of simulation research can be an instruction to develop new design of cementless design to both achieve less invasive surgery and excellent duration.